ICPC: an analytical discourse of its practice, procedure and mechanisms (2013)
Corruption is not only antithetical to the Nigeria's economic and political development, it also manifests social injustice and is symptomatic of societal decay. The enactment of the Corrupt Practices and Other Related Offences Act, 2000 which creates the Independent Corrupt Practices and Other Related Offences Commission (ICPC), is a major move by the Nigerian government to tackle the hydra-headed problem of corruption through the instrumentality of law. This paper examines the practice, procedure and mechanisms of the ICPC and offers suggestions for improvement.